2006
DOI: 10.1101/gad.1400506
|View full text |Cite
|
Sign up to set email alerts
|

Novel arylpyrazole compounds selectively modulate glucocorticoid receptor regulatory activity

Abstract: The activities of intracellular receptors are regulated by their cognate ligands. Here we show that a series of related arylpyrazole compounds, which specifically bind the glucocorticoid receptor (GR), selectively modulated GR-regulated biological functions in preadipocyte, preosteoblast, and lung epithelial cell lines. Indeed, when we monitored 17 endogenous GR target genes in one of these cell types, we found that distinct arylpyrazole compounds induced different expression patterns. We showed by chromatin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 34 publications
3
72
0
3
Order By: Relevance
“…Much of the work in this area has centered about the development of unique GR-binding ligands that display a more selective gene-regulation pattern than classical GCs. The end result of this body of effort has demonstrated that the problem is complex, because slight alterations in ligand structure and chemical reactivity can have a pronounced influence on the transcriptional regulatory activity of GR (14). An additional complication to mechanistic study of the GR is the fact that examples have been noted in which genes are repressed through DNA-binding dependent GR action, in addition to those in which genes are activated through DNA-binding independent action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the work in this area has centered about the development of unique GR-binding ligands that display a more selective gene-regulation pattern than classical GCs. The end result of this body of effort has demonstrated that the problem is complex, because slight alterations in ligand structure and chemical reactivity can have a pronounced influence on the transcriptional regulatory activity of GR (14). An additional complication to mechanistic study of the GR is the fact that examples have been noted in which genes are repressed through DNA-binding dependent GR action, in addition to those in which genes are activated through DNA-binding independent action.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the mechanisms of GR activity on target genes has been explored using a variety of approaches, including microarray analysis (10,11); ChIP scanning (12); and modulation of GR activity using siRNA (13), genetic mutants (4), and ligands with modified structures (14). However, these methods would not be expected to differentiate explicitly between the direct and indirect DNA-binding mechanisms of GR action.…”
mentioning
confidence: 99%
“…The outcome of a potential 9cRA/atRA interaction with pancreas RARs cannot be predicted simply because both retinoids bind to the same receptor. Nuclear receptor action depends on the ligand bound and the nucleotide sequence of the gene's response element-both influence receptor conformation, affinity for a particular response element, and function (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of AL-438 involves differential coactivator recruitments of GRIP1/ TIF2 versus PGC-1; the latter seems preferentially used in steroid-mediated glucose upregulation (Coghlan et al, 2003). Third, a series of related arylpyrazole compounds can elicit different expression patterns on 17 endogenous GR target genes in different cell types (i.e., lung, preadipocyte and preosteoblast), demonstrating that subtle differences in ligand structure can have profound effects on transcriptional regulatory activities of NRs (Wang et al, 2006).…”
Section: Selective Nr Modulatorsmentioning
confidence: 99%